Nontoxic Cobalt(III) Schiff Base Complexes with Broad‐Spectrum Antifungal Activity. Issue 6 (24th November 2020) - Frei, Angelo; King, A. Paden; Lowe, Gabrielle J.; Cain, Amy K.; Short, Francesca L.; Dinh, Hue; Elliott, Alysha G.; Zuegg, Johannes; Wilson, Justin J.; Blaskovich, Mark A. T.
Abstract: Resistance to currently available antifungal drugs has quietly been on the rise but overshadowed by the alarming spread of antibacterial resistance. There is a striking lack of attention to the threat of drug‐resistant fungal infections, with only a handful of new drugs currently in development. Given that metal complexes have proven to be useful new chemotypes in the fight against diseases such as cancer, malaria, and bacterial infections, it is reasonable to explore their possible utility in treating fungal infections. Herein we report a series of cobalt(III) Schiff base complexes with broad‐spectrum antifungal activity. Some of these complexes show minimum inhibitory concentrations (MIC) in the low micro‐ to nanomolar range against a series of Candida and Cryptococcus yeasts. Additionally, we demonstrate that these compounds show no cytotoxicity against both bacterial and human cells. Finally, we report the first in vivo toxicity data on these compounds in Galleria mellonella, showing that doses as high as 266 mg kg −1 are tolerated without adverse effects, paving the way for further in vivo studies of these complexes. Abstract : Metals vs. fungi : Given that metal complexes have proven to be useful new chemotypes in the fight against diseases such as cancer, malaria, and bacterial infections, it is reasonable to explore their possible utility in treating fungal infections. Herein we report a series of cobalt(III) Schiff base complexes with broad‐spectrum antifungal activity against Candida and Cryptococcus yeasts, with MICs in the low micro‐ to nanomolar range.